2022
DOI: 10.1088/1361-6455/ac8213
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of the radiative properties of NO—a first step toward a complete air opacity

Abstract: In this paper we propose a methodology to calculate the radiative properties of the diatomic molecular constituents of air, and utilize the present approach to model the radiative properties of nitrogen monoxide, NO. We also investigate the important physics involved in calculating accurate radiative quantities for air, such as the Planck and Rosseland mean opacities, and emission and absorption coefficients, as well as the couplings accounted for in rovibrational calculations. Complete active space self-consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 217 publications
0
4
0
Order By: Relevance
“…The m values can be used to predict spectra, opacities, and radiative properties of molecular species and hence are often calculated using ab initio techniques. [50][51][52][53] The MRCI DMCs of the first five electronic states of HfN are given in Fig. 5.…”
Section: Iiia Hfnmentioning
confidence: 99%
“…The m values can be used to predict spectra, opacities, and radiative properties of molecular species and hence are often calculated using ab initio techniques. [50][51][52][53] The MRCI DMCs of the first five electronic states of HfN are given in Fig. 5.…”
Section: Iiia Hfnmentioning
confidence: 99%
“…The calculated MQDO electronic transition moment is 0.34 a.u. This value is in good agreement with the CAS-MRCI results at the equilibrium position of Cooper (1982), 0.34 a.u., andZammit et al (2022), 0.36 a.u., and with the adjusted empirically CAS-MRCI result of 0.30 a.u. of Qu et al (2021aQu et al ( , 2021b.…”
Section: Tablementioning
confidence: 99%
“…Regarding the theoretical data available, our result is in reasonable good agreement with the band f -values of 0.00220 and 0.00249 reported by Galluser &Dressler (1982) andDe Vivie &Peyerimhoff (1988), respectively. Zammit et al (2022) reported a value of 0.0025 for the rotationally averaged absorption oscillator strength of the diabatic C 2 Π(0)-X 2 Π(0) transition. Therefore, the electronic transition moment, overlap integrals, and eigenvector components obtained in this work seem to be accurate.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation